(untitled) (Journal of Pathology of Nepal, 2012)
Background: Typhoid fever continues to be a worldwide health problem, especially in developing countries. Effective epidemiological surveillance is needed to monitor the presence and spread of disease. Materials and Methods: Variable number tandem repeats (VNTR) was performed for Salmonella enterica serovar typhi by multiplex-PCR in 28 Nepalese isolates of sporadic typhoid fever. Results: From all 28 total isolates, we could identify 12 VNTR profiles among the isolates, signifying multiple variants in circulation within the region. Conclusion: The VNTR-based typing assay for serovar typhi isolates can be used during an outbreak of enteric fever. The typing could eventually form the basis of an effective epidemiological surveillance system for developing rational strategies to control typhoid fever. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6026 JPN 2012; 2(3): 220-223